Electrical design of large‐scale tubular PM linear generators for wave energy conversion. (8th December 2017) - Jing, Hailian; Maki, Naoki; Ida, Tetsuya; Izumi, Mitsuru
Abstract : We propose a novel conceptual structure of a large‐scale wave energy converter (WEC) and develop an electrical design method for tubular permanent magnet linear generators (PM‐LGs) adopted in the WEC. We describe the electrical design method of the PM‐LGs in detail, with design results of 1 MW PM‐LGs presented. Magnetic flux distribution obtained by the simulation is further analyzed, which shows good agreement with the design results. The electrical design method of large‐scale PM‐LGs described in this paper provides a reference to design large‐scale electric machines.